Pengaruh Efektifitas Disiplin kerja Terhadap Kinerja guru Di Taman Kanak-Kanak Kecamatan Kepenuhan Hulu, Rokan Hulu - Tri Kumala Dewi; Nurhafizah; Dadan Suryana (Universitas Pendidikan Ganesha, 2023)
The lack of discipline of an educator in the school environment makes the learning process less quality. This research aims to analyze the effectiveness of work discipline on teacher performance in Kindergarten. This type of research is quantitative with a survey method. The number of samples used was from each school consisting of 3 people (principal, TU, and school guard). The total number of teachers is 45, and the questionnaire is a rating scale model. Respondents were 25 teachers. The data collection method is a non-test method. The research instrument used was a questionnaire. Data analysis techniques with quantitative and qualitative analysis. Based on the results of data analysis, it is known that the influence of work discipline on teacher performance is 0.288, equal to 28.8%. The test results show that work discipline directly influences teacher performance. Thus, work discipline, as reflected in awareness, willingness, obedience, and work ethics, has a positive and significant effect on teacher performance as reflected in work quality, work accuracy, initiative in work, workability, and communication. The implications of the work discipline of a teacher who can complete and implement learning activities that are interesting and not boring for children and obey the rules.